X-Ray diffraction and scanning electron microscopy-energy dispersive spectroscopic analysis of ceramõmetal interface at different firing temperatures - Monika Saini; Suresh Chandra; Yashpal Singh; Bikramjit Basu; Arvind Tripathi (Wolters Kluwer Medknow Publications, 2010)
Objective: Porcelain chipping from porcelain fused to metal restoration has been Achilles heel till date. There has been advent of newer ceramics in past but but none of them has been a panacea for Porcelain fracture. An optimal firing is thus essential for the clinical success of the porcelain-fused to metal restoration. The aim of the present study was to evaluate ceramo-metal interface at different firing temperature using XRD and SEM-EDS analysis. Clinical implication of the study was to predict the optimal firing temperature at which porcelain should be fused with metal in order to possibly prevent the occasional failure of the porcelain fused to metal restorations. Materials and Methods: To meet the above-mentioned goal, porcelain was fused to metal at different firing temperatures (930-990°C) in vacuum. The microstructural observations of interface between porcelain and metal were evaluated using X-ray diffraction and scanning electron microscopy with energy dispersive spectroscopy. Results: Based on the experimental investigation of the interaction zone of porcelain fused to metal samples, it was observed that as the firing temperature was increased, the pores became less in number as well as the size of the pores decreased at the porcelain/metal interface upto 975°C but increased in size at 990°C. The least number of pores with least diameter were found in samples fired at 975°C. Several oxides like Cr 2 O 3 , NiO, and Al 2 O 3 and intermetallic compounds (CrSi 2 , AlNi 3 ) were also formed in the interaction zone. Conclusions : It is suggested that the presence of pores may trigger the crack propagation along the interface, causing the failure of the porcelain fused to metal restoration during masticatory action.